Análisis de movilidad para la Zona Céntrica (Norte Av. La Prensa, Sur Calle Juan de Velasco, entre la Calle José de Orozco y Oeste con la Calle José Joaquín de Olmedo) de la ciudad de Riobamba perteneciente a la Provincia de Chimborazo. - Rojas Tixe, Luis Alberto (2016)
: When analyzing mobility for the downtown area (North av. La Prensa, South Street Juan de Velasco, between the street José de Orozco and West with the street Jose Joaquin de Olmedo) of Riobamba city in Chimborazo province each part comes with numbers as a result and manifestation of each of the realities studied and planned. As you can see the Plan is comprehensive and coherent between the component parts, both, in terms of the public space and mobility. It responds to a model that aims to improve urban and life quality of citizens and simultaneously improve the functionality and organization of the urban system of the Riobamba city. Proposals draw a new mobility model since the percentages travel between different modes of transport that which are modified. The number of trips of private transport is reduced to the benefit of more sustainable modes of transport. Also they draw a new public space with a cast for their current uses and different functions. This means that the citizen (it is because it deals public space without restrictions) to reacquire his letter of nature in most of the public space. A high quality public space, without noise, pollution, safe, attractive and power contact and coexistence among people of all ages and social status. The citizen is no longer street walker, it is no longer just a place of passage, it is a place and most of all stay and coexistence is where most urban functions can be developed. Finally it has been concluded and recommended this work as a strategic means for the city of Riobamba and as a theoretical and intellectual use in your training.